A Correlation Among the Increased Temperatures Toward the Productivity of Ladang in Kutai Barat Regency, the province of East Kalimantan - Sujalu, Akas Pinaringan (Journal of Agricultural Sciences (Belgrade), 2019)
The studies on the impact of global warming in particularly food production could provide more accurate analysis to support a policy of food security. This research was conducted to find out the trends and the impact of the increase in the air temperature toward the production of ladang (swidden field) in the Kutai Barat Regency. The result of the research done to some of the traditional rice fields indicates it has technology barely changes prominently, and fixed-based organic cultivation. During the years 1990-2015 air temperature increased daily average of 21.20C-25.20C or an average increase 0.160C/year. In the same period increased the productivity of ladang  1.87-3.19 tons/hectares or an average increased 0.26 tons/hectare/year. Linear regression analysis results on the level of significance of 5% showed the existence of the real correlation (r=0.7) between the average air temperature change and the productivity of the paddy fields.